Evolving plasma sensors for future measurements of Earth’s magnetospheric cold plasma - Justin H. Lee; Joseph F. Fennell; Colby L. Lemon; William R. Crain; Susan H. Crain; Spencer Bell; Geoffrey A. Maul; Julian R. Lohser (Frontiers in Astronomy and Space Sciences)
Routine measurements of Earth’s magnetospheric cold plasma have not occurred on any recent space science mission. This hurdle to cold plasma science progress spans decades, root cause linked to space system and space environment interactions that compromise the conditions for acquiring cold plasma measurements. Focused efforts must still develop and mature techniques, methods, or technologies to overcome the complex sensor operating conditions that arise from these interactions. This Perspective article provides common and recent examples of observed experimental data artifacts caused by spacecraft- or sensor-environment interactions to remind us of the ensuing degradation in accuracy of magnetospheric cold plasma measurements. We then describe one angle of attack leveraging instrument technology development in progress today that can help improve measurement conditions for future sensors. Our Perspective can motivate parallel developments or application of such technologies to future science investigations.